Performance of Laying Hens Fed Varying Dietary Levels of Bambara (Voandzeia subterrenea Thouars) Offals - Onyimonyi, A.E.; Ugwu, S.O.C. (International Journal of Poultry Science, 2007)
A feeding trial was conducted to evaluate the performance of laying hens fed varying dietary levels of Toasted Bambara Offals (TBO). The TBO was included in the diet at five levels of 0, 5, 10, 15 and 20 percent. A total of ninety laying hens on their eight week of lay were used for the trial that lasted for 133 days. The ninety birds were randomly assigned to the five dietary levels (0, 5, 10, 15 and 20 percent) with 18 birds per levels. Each dietary level was further replicated four times in a completely randomized design. Results showed that egg weight (g), yolk weight (g) and albumen weight (g) were significantly (P